Cargo management optimization using heuristic approach - Arcano, Earl; Lazo, John Christopher;Ritual, Niel Arvin (Manila : National University, 2013)
Logistics can be defined as transporting the right type of products and/or services at the right price, place, time and in the right condition. It is also defined as science of transporting, organizing, and managing activities that provide goods and services. A quick look back at some logistics history may prove very enlightening.
Title page -- Chapter 1 : Context of the study -- Statement of the problem -- Objectives of the study -- Scope and delimitation -- Significance of the study -- Motivation -- Chapter 2 : Related literature -- Related studies -- Conceptual framework -- Operational definition of terms -- Chapter 3 : Methods of research -- Process flow diagram -- Testing procedure -- Project design development -- Evaluation procedure -- Respondents of the study -- Statistical treatment of data -- Liker's scale -- Percentage distribution -- Chapter 4 : Existing system -- Proposed technology -- Proposed system -- Chapter 5 : Login interface -- Main menu -- Delivery -- Report -- User maintenance -- Location update -- Appendices -- Bibliography -- Curriculum vitae.
Includes bibliographical references.